2021
DOI: 10.1186/s12871-021-01233-9
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcomes in surgical COVID-19 patients: a multicenter cohort study

Abstract: Background Data on postoperative outcomes of the COVID-19 patient population is limited. We described COVID-19 patients who underwent a surgery and the pandemic impact on surgical activities. Methods We conducted a multicenter cohort study between March 13 and June 192,020. We included all COVID-19 patients who underwent surgery in nine centres of the Province of Québec, the Canadian province most afflicted by the pandemic. We also included concomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 30 publications
(39 reference statements)
7
40
1
Order By: Relevance
“…In this case, surgery was performed 18 days (within 4 weeks) after the isolation of the patient. According to previous reports, from the viewpoint of safety, surgery is not recommended until at least 4 weeks after the symptoms of COVID-19 resolve [3,5]; however, this "fourweek rule" lacks sufficient evidence because of the small number of cases. Should patients previously infected with COVID-19 have to wait to be operated on for more than 4 weeks?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, surgery was performed 18 days (within 4 weeks) after the isolation of the patient. According to previous reports, from the viewpoint of safety, surgery is not recommended until at least 4 weeks after the symptoms of COVID-19 resolve [3,5]; however, this "fourweek rule" lacks sufficient evidence because of the small number of cases. Should patients previously infected with COVID-19 have to wait to be operated on for more than 4 weeks?…”
Section: Discussionmentioning
confidence: 99%
“…Although routine evaluation of tolerance for general anesthesia and surgery was performed with blood tests, electrocardiogram, and X-ray, additional venous ultrasound and chest CT scan were needed because of the previous COVID-19 infection. Preoperative screening tests involving venous ultrasound for thrombosis from coagulopathy and chest CT scans for respiratory failure, which are the main causes of postoperative complications in patients infected with COVID-19 [3,5], were important. It was previously reported that pulmonary complications occurred in 18.5%, 11.7%, and 0.0% of patients who were operated on 1-2 weeks, 2-4 weeks, or more than 4 weeks, respectively, after the resolution of COVID-19 symptoms [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that co-infection did not result in more complications for emergency abdominal surgery, although an acute abdomen with severe COVID-19 had dismal prognosis. In a multicenter cohort study conducted by Carrier et al [18], they analyzed 44 patients with COVID-19, with 31 surgeries (71%) being urgent. They described that the postoperative 30-day mortality in COVID-19 patients undergoing surgery was high (15.9%).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis reported a surprising finding, 28 out of 269 patients with COVID-19 infection died from postoperative complications associated with COVID-19, such as respiratory failure and acute respiratory distress syndrome (ARDS)[ 11 ]. A multicenter cohort study in Canada reported that postoperative 30-day mortality in COVID-19 patients was notably high (15.9%)[ 12 ]. To date, several researchers have warned of the increased risk of postoperative mortality in patients with COVID-19 infection and have elucidated the characteristics of high-risk patients[ 9 , 13 - 15 ].…”
Section: General Considerations Regarding Postponement Of Pancreatic Surgerymentioning
confidence: 99%